PERBANDINGAN RENCANA ANGGARAN BIAYA PADA PERHITUNGAN TEBAL LAPIS TAMBAH (OVERLAY) DENGAN METODE PD T-05-2005-B DAN ASPHALT INSTITUTE MS-17 - J.M, Satria Agung Mulia; Iriana, Rian Trikomara; Shalahuddin, M (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The purpose of this study is to analyze the budget plan obtained from the overlay calculation using Pd T-05-2005-B and the Asphalt Institute MS-17. Studies were conducted on roadsections of Jurong-Mandau in Bengkalis, regency using design life of 5 years and 10 years with traffic development rate 5.165%, which is projected from the linear regression. Theresults of this study with Pd T-05-2005-B methods design life of 5 years, segment 1 sta 00+000 s/d 00+500 by 7.770 cm, segment 3 sta 02+500 s/d 03+000 by 8.467 cm with a total cost of Rp. 2,873,439,898.00 and a design life of 10 years obtained overlay, segment 1 sta 00+000 s/d 00 + 500 by 10.624 cm, segment 3 sta 02+500 s/d 03+000 by 11.201 cm, the segment 9 sta 06+000 s/d 06+500 by 3,810 cm with a total cost of Rp. 4,003,870,931.00.And then with Asphalt Institute MS-17 method design life of 5-year and 10 years does not require an overlay and budget plan calculations, because from the calculations obtained overlay value is 0. Based on the results of the study indicate that working on overlay design life of 10 years is more economis and effective than the design life of 5 years.Keywords: Overlay, Budget Plan, Design Life, Pd T-05-2005-B Method, Asphalt Institute MS-17 Method.